Evaluasi Postur Kerja Operator Book Lift Menggunakan Pendekatan Rapid Upper Limb Assessment (RULA) - Alex Alfandianto; Cosmas Eko Suharyanto; Chosmas Marzuki (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2021)
Incorrect work posture is often caused by stations and work facilities that are not suitable for workers, this period is an important factor for companies that do not pay attention to the needs and interests of workers. There are still many companies whose work processes are not supported by standard methods and ergonomic work facilities so that workers often complain about their body parts. Complaints that arise due to the absence of ergonomic work facilities that are in accordance with the worker's body posture, causing workers to feel uncomfortable. The working posture that needs to be evaluated using the Rapid Upper Limb Assessment (RULA) method is bending and squatting because it provides the highest value. The value of work posture presented in the RULA method obtained from the operator's lift book is a grand score of 6. The immediate position of the body is to add work facilities in the form of table scissors so that there is no potential for injury when lifting and carrying books.